A Comparison between Total Phenols and Total Alkaloids Antibacterial Activity Extracted from Bulbs of Narcissus tazetta L - Mohammed Hasan, Zainab Yaseen; Ola Kareem Ali; Arwa Abdul-Kareem Tawfiq (Iraqi Journal of Pharmaceutical Sciences, 2023)
Narcissus tazetta plant from Amaryllidaceae family is known to be rich in bioactive metabolites such as Alkaloids, phenolics and flavonoid which detected in almost species of this family. N. tazetta cultivated in Iraq, had not yet been studied for its active components as antimicrobial; thus the current study employed the antibacterial activity for total phenolic compounds and total alkaloids extracted from this plant. The plant bulb pieces were defatted with n-hexane before extraction of total phenols(TP) and total alkaloids(TA) from the plant. Results showed that the plant contains about 0.95g/140g bulb as total phenols residue and 0.7g/150g bulb as total alkaloids residue. The major Tp compounds observed in HPLC assay were Salycilic acid, Sinapic acid, vanillic acid, Caffeic acid, Chlorogenic acid, and p-coumaric acid in desending quantity. Four layer had been collected that might contain different kinds of alkloids. The methanolic layer (1) and layer (3) which represented the chloroform layer after acidification represented the richest layers in ’Glanthamine’ alkloid represented by HPLC assay. The antibacterial as inhibitory effects of TP and TA on E.coli, P.auroginosa, S.aureus and Bacillus subtillus, showed moderate antibacterial activity for both plant extracts in coparisin to some trade antibiotics.